Pulse pressure in acute coronary syndromes: Comparative prognostic significance with systolic blood pressure. Issue 4 (June 2019) - Tan, Nigel S; Sarak, Bradley; Fox, Keith AA; Brieger, David; Steg, Ph. Gabriel; Gale, Chris P; Bhatt, Deepak L; Spencer, Frederick A; Grondin, Francois R; Goodman, Shaun G; Yan, Andrew T; ,
Background: Pulse pressure is a readily available vital sign that has been shown to independently predict outcomes in several cardiovascular disease states. We investigated the prognostic significance of pulse pressure (PP) and systolic blood pressure (SBP) among patients with acute coronary syndromes (ACS). Methods: A total of 14, 514 patients with ACS in the prospective, multicentre Global Registry of Acute Coronary Events (GRACE), expanded GRACE (GRACE-2) and Canadian Registry of Acute Coronary Events (CANRACE) were stratified by initial PP on presentation. Patient characteristics and in-hospital outcomes were compared by PP quartiles and the independent prognostic significance of PP for in-hospital mortality was quantified. We compared the discriminative ability (c-statistic) of models incorporating either PP or SBP. Results: Patients with higher PPs were older, more frequently female and had higher prevalence rates of conventional cardiovascular risk factors (all p < 0.01). Lower PP was associated with ST-segment elevation myocardial infarction presentation, higher GRACE risk scores and higher rates of adverse in-hospital outcomes ( p < 0.001). PP was strongly correlated with SBP (Pearson's correlation coefficient = 0.79, p < 0.001). After adjustment for other GRACE risk model predictors, lower PP was independently associated with in-hospital mortality (first vs. fourth quartile [reference]: adjusted odds ratio 2.57, 95% confidence interval 1.80–3.67). The c-statistic was slightly higher for the multivariable model incorporating SBP as compared to the model with PP (0.868 vs. 0.864, respectively, p = 0.028) for in-hospital mortality. Conclusion: Higher presenting PP is associated with increased age and more prevalent cardiovascular risk factors, whereas patients with lower PP present with worse clinical characteristics and in-hospital outcomes. Lower PP is an independent adverse prognosticator in ACS. However, PP did not improve the discriminatory performance of the GRACE risk score compared with SBP.